Using SFL in an appliable stylistics: Exploring verbal artistry and its implications for poetic translation. (21st May 2015) - Lin, Benedict
Abstract : As an applied discipline, modern stylistics has made significant attempts to contribute to literary interpretation, literary criticism and literature pedagogy. However, its potential contribution to literary translation, and in particular, poetic translation, remains underexplored. In this paper, I demonstrate through the case study of a Tang Dynasty poem and one of its translations how Hasan's (1985) SFL-based framework for the analysis of verbal art constitutes the basis of a potentially powerful and appliable stylistics that lays bare issues related to the (re-)construction of verbal artistry in translation. Hence, I argue that Hasan's model can make a valuable contribution to the field of literary translation, and call for greater extension of her work to this domain.